SEISMICITY ANALYSIS AND DETERMINATION OF FOCAL MECHANISM OF EARTHQUAKE IN SUMEDANG USING MOMENT TENSOR INVERSION METHOD - Paris Stefanus, Piero
An earthquake with a magnitude of 4.6 that occurred in the Sumedang area, West Java, at the end of 2023 caused shocks that were felt as far away as Bandung and its surroundings. According to BMKG, this earthquake was caused by active fault activity that had not previously been identified. To record aftershocks, the ITB Seismology Team installed 22 Smartsolo earthquake recording stations, which operated from January 2 to January 27, 2024. This study aims to analyze aftershock activity and the focal mechanism of the Sumedang earthquake. A total of 40 aftershock events were successfully identified using automatic and manual detection methods. Determination of the arrival time of P and S waves was carried out manually using Seisgram2K software and Wadati diagram analysis. The focal mechanism was determined using the moment tensor inversion method with ISOLA software. The analysis results show that six out of ten earthquake events with a magnitude >2 illustrate the complexity of the focal mechanism of the alleged Sumedang Fault. The distribution of hypocenters, focal mechanism maps, and geological data confirm the existence and movement of the Sumedang Fault. These findings provide an important contribution to the understanding of the tectonics of the Sumedang region and disaster mitigation efforts in the surrounding area.